Adminsitration of educational facilites and infrastructure management in improving the quality of leraning in Madrasah Ibtidaiyah - Mursal Aziz; Masriana Masriana; Putri Utami; Raya Marcela (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
This research is entitled "Management of Educational Facilities and Infrastructure to Improve the Quality of Learning at MIN 3 Labuhan Batu". In the learning process, facilities and infrastructure are very necessary for schools to support the success of learning activities. The aim of this research is to determine: (1) management of educational facilities and infrastructure, (2) efforts made to improve the quality of learning . This research uses a descriptive method with a qualitative approach. The subject of this research is the deputy head of the facilities and infrastructure division of MIN 3 Labuhan Batu, while the object of this research is the management of educational facilities and infrastructure to improve the quality of learning. Data collection was carried out by observation, interviews and documentation. The results of this research show that: (1) Management of educational facilities and infrastructure is carried out by involving all school components such as principals, deputies and teachers, for procurement based on prioritized needs and adjusted to funds, both BOS funds and assistance from other parties. other. Then it is recorded in the inventory book for a period of one year. Meanwhile, deletion has never been carried out until now. (2) The efforts made are to equip educational facilities and infrastructure and motivate students to be more active in studying.